Beyond the Lantern Festival: Designing Fantasy Illustrations Inspired by Lontong Cap Go Meh and Kelenteng Hok An Kiong - Sutanto, Shienny Megawati; Mudra, I Wayan; Udayana, A. A. Gde Bagus; Suardina, I Nyoman (VCD: Journal of Visual Communication Design, 2024)
This study examines the creative process behind the illustrations of the fantasy novel "Warisan Dua Dunia" inspired by the Lontong Cap Go Meh tradition in Hok An Kiong Temple, Surabaya. This tradition is an interesting example of Indonesian and Chinese cultural acculturation. A qualitative descriptive method with observation, interview, and documentation techniques was used in this study. The theoretical framework used includes Visual Language (Tabrani) and The Big Triangle (Mc Cloud). The results showed that the creative process of the novel illustration began with observation and reflection on the Lontong Cap Go Meh tradition. The researcher combined the results of observation and reflection with personal experience to form a personal interpretation visualized in a manga style. Imaginative and realistic visualizations inspired by Chinese culture enrich the work's aesthetics and transport the reader into an imaginary world full of meaning. This study shows that the combination of contemplation, personal interpretation, and manga visual style produces a work that is not only relevant to the younger generation but also opens up new interpretation towards tradisi Lontong Cap Go Meh di Kelenteng Hok An Kiong.